Peculiarities of people mortality in the Tomsk Region and main ways of its decrease - S. Yu. Kladov; I. N. Konobeyevskaya; R. S. Karpov (Бюллетень сибирской медицины)
Peculiarities in the structure of mortality of people living in the Tomsk Region have been revealed, and main ways to decrease the mortality have been determined. In 2002 the death rate in the Tomsk Region was 14.3 per 1000 people, which is lower than the average Russian death rate (16.3). The analysis of death causes has shown that the most frequent causes are diseases of the blood system, while the second and third places are occupied by the death from neoplasm, as well as from accidents, poisoning, and traumas.The health factor should become of the high priority in all spheres of human activity. Any measure should favor the formation of the healthy life style and everybody’s personal responsibility for the health. It is worth developing the interbranch demographic concept of the Tomsk Region as an integral part of the concept of the enhancement of life quality for people living in the Tomsk Region.